The establishment of the Onthophagus anthracinus (Coleoptera: Scarabaeidae) species complex and the description of a new species. Issue 1 (16th February 2020) - Arriaga-Jiménez, Alfonsina; Escobar-Hernández, Fernando; Rös, Matthias; Kohlmann, Bert
Abstract: The Onthophagus anthracinus Harold, 1873 (Coleoptera: Scarabaeidae: Scarabaeinae: Onthophagini) species complex of the Onthophagus landolti Harold, 1880 species group is established and analysed. A new species, O. etlaensis, is described from this group. Onthophagus mextexus Howden and Cartwright, 1970 is considered a valid species and O. knulli Howden and Cartwright, 1963 is placed in synonymy with O. durangoensis Balthasar, 1939 new synonymy . A key for the O. anthracinus species complex is presented along with photographs and illustrations of the main taxonomic differences. An update of the O . landolti species group is presented.